2014
DOI: 10.3109/08820538.2014.962176
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Keratitis Following Corneal Crosslinking: A Systematic Review of Reported Cases: Management, Visual Outcome, and Treatment Proposed

Abstract: Only 10 cases of infectious keratitis following corneal crosslinking are published. The most virulent pathogens were Pseudomonas aeruginosa and Acanthamoeba. Less virulent organisms were Escherichia coli and S. epidermidis. Two cases of herpes keratitis were described, suggesting the possibility of systemic antiviral prophylaxis before corneal crosslinking treatment. The most common risk factor of infections identified was postoperative incorrect patient behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 42 publications
1
33
2
1
Order By: Relevance
“…Although postoperative complications such as infection,11 persistent corneal oedema12 and need for keratoplasty19 have been reported more frequently with epithelium-off CXL techniques, our study did not demonstrate a difference between the epithelium-off CXL group and the transepithelial CXL group. However, the postoperative complication rate was very small for our overall study population, suggesting that a much larger number of study subjects would be required to effectively compare the rate of postoperative complications between CXL techniques.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Although postoperative complications such as infection,11 persistent corneal oedema12 and need for keratoplasty19 have been reported more frequently with epithelium-off CXL techniques, our study did not demonstrate a difference between the epithelium-off CXL group and the transepithelial CXL group. However, the postoperative complication rate was very small for our overall study population, suggesting that a much larger number of study subjects would be required to effectively compare the rate of postoperative complications between CXL techniques.…”
Section: Discussioncontrasting
confidence: 72%
“…In the Dresden CXL method, the corneal epithelium was removed prior to administration of the riboflavin solution and ultraviolet A irradiation 10. However, several complications associated with surgical debridement of the epithelium have been reported using this technique 11 12. In an attempt to avoid complications associated with epithelial debridement and to allow for less postoperative discomfort and quicker recovery times, researchers have recently described a method in which the corneal epithelium is left intact using a transepithelial approach 13 14…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to stop the progression of ectasia, and studies reported persistent effects up to 7 years after treatment [2, 3]. Corneal CXL was also used to manage iatrogenic ectasias [3], pellucid marginal degeneration [19], infectious keratitis [4] or even bullous keratopathy [20]. It is believed to delay or even avoid invasive surgical procedures such as corneal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 20 years, strengthening the biochemical and biomechanical properties of the cornea by collagen cross-linking (CXL) has become one of the very effective treatments to stop progression of keratoconus [1, 2], corneal ectasia [3], and even in the treatment of some forms of resistant infectious keratitis [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Epithelium removal creates a variety of risks such as infiltrates, delayed reepithelialization and infectious keratitis [22]. Corneal haze following CXL has been studied, although its impact on vision is not established [23].…”
Section: Corneal Cross-linking Safety Parametersmentioning
confidence: 99%